An Optimized Load Shedding Approach in Power Grids to Mitigate Cascading Failure - Ahmed M. A., Haidar; Andreas, Helwig; Liviu, Moldovan (2025)
Power grid security has always been a key issue in power industry development. The paper presents an optimal approach to mitigate power blackouts by applying steady-state load shedding. The particle swarm optimization algorithm is employed in cloud computing and monitoring environments to minimize the amount of power to be shed and its location. The standard IEEE test systems have been used as a benchmark to validate the proposed approach. The preliminary results show that the system’s parameters are constrained within the safety limit. Thus, reserve generation remains connected to the power grid for additional service during grid faults. The proposed modeling and control can be used to develop planning and operational strategies for a practical power system. Features related to integrating advanced digital solutions to enhance the power grid operation and reduce downtime by improving real-time monitoring and data-driven approaches are also presented.